A Review of Islamic Economic Law on The Structure of the Samsarah Contract and Marketing Strategies at Propertindo Friday Agency - Nabila Sakinah; Ali Aminulloh; Siti Ngainur Rohmah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
Marketing strategy is a series of business activities that include planning, pricing, promotion, and distribution of goods or services to meet consumer needs. In its implementation, marketing strategies should adhere to ethical principles and Islamic Economic Law to ensure that business activities are conducted in a lawful, fair, and sustainable manner. As a property agency located in Bekasi City, Propertindo Friday applies modern digital marketing to expand promotional reach and improve sales effectiveness. This study aims to analyze the practice of the samsarah (brokerage) contract between Propertindo Friday and PT Mulqi from the perspective of DSN-MUI Fatwa No. 151/DSN-MUI/VI/2022, as well as to examine the marketing strategies employed by Propertindo Friday in increasing property sales from the perspective of Islamic Economic Law. This research employs a descriptive qualitative method. The study utilizes two types of data sources: primary data obtained through observation and interviews, and secondary data obtained from books, journals, and legislation. Data were collected through observation, in-depth interviews, and documentation. To ensure data validity, the researcher applied source triangulation by verifying information through multiple data sources. The cooperative relationship between Propertindo Friday and the developer is established through a samsarah contract, which creates responsibilities for the agency to market properties professionally, honestly, and in accordance with the agreed terms. These responsibilities are implemented through the application of the marketing mix (4P) strategy, supported by digital media and TikTok live streaming as efficient and interactive promotional tools. From the perspective of Islamic Economic Law, these marketing practices reflect the values of honesty (sidq), communication (tabligh), and trustworthiness (amanah), both in the relationship between the agency and the developer and in services provided to consumers. Therefore, Propertindo Friday’s marketing strategy is aimed not only at increasing sales but also at maintaining business ethics and achieving blessings in accordance with Islamic principles. Keywords: Property, Samsarah, Marketing, Islamic Economic Law.